PEDAGOGICAL APPROACHES IN TEACHING FOREIGN LANGUAGES - Mirzaahmedova Sevinch; Igamberdieva Shahnoza (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
The article describes ways to improve the quality of education of teachers of English in secondary schools through the use of innovative methods and examines the role of activity centers in the organization of classes in preschool education and the role of the state educational program "First Step" in the comprehensive development of children’s abilities and skills in the educational process.